2013
DOI: 10.1016/j.clnu.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D supplementation during a resistance training intervention on body composition, muscle function, and glucose tolerance in overweight and obese adults

Abstract: Background & Aims The impact of vitamin D supplementation in overweight and obese adults during resistance training on body composition, muscle function, and glucose tolerance was investigated. Methods Twenty-three overweight and obese (age: 26.1±4.7 y; BMI: 31.3±3.2 kg/m2; 25-hydroxyvitamin D: 19.3±7.2 ng/mL) adults were recruited for participation in a double-blind, placebo-controlled trial. Participants were randomly divided into vitamin D (VitD, 4000 IU/d; 5 female, 5 male) and placebo (PL; 7 female, 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(92 citation statements)
references
References 27 publications
(41 reference statements)
5
82
3
Order By: Relevance
“…As a result, a total of 18 publications were included in this report, with 11 of them being included in the meta-analysis of PTH responses by vitamin D supplementation, three included in the analysis of PTH responses by vitamin D and calcium supplementation, and the other four being analyzed qualitatively. Table 1 [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33] shows the publications included in this report in the order they were retrieved. The table lists the sample size, mean BMI, mean change in PTH and 25OHD, as well as baseline and end of study results for PTH and 25OHD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, a total of 18 publications were included in this report, with 11 of them being included in the meta-analysis of PTH responses by vitamin D supplementation, three included in the analysis of PTH responses by vitamin D and calcium supplementation, and the other four being analyzed qualitatively. Table 1 [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33] shows the publications included in this report in the order they were retrieved. The table lists the sample size, mean BMI, mean change in PTH and 25OHD, as well as baseline and end of study results for PTH and 25OHD.…”
Section: Resultsmentioning
confidence: 99%
“…For determining the responses of PTH due to combined vitamin D-calcium supplementation, two studies that examined three different groups of overweight and obese participants that met the inclusion criteria were included in the meta-analysis (total N = 337, Figure 6) [27,33]. The Cochran’s Q was significant, Q(2) = 146.59, p < 0.001.…”
Section: Resultsmentioning
confidence: 99%
“…Carrillo et al [49], demonstrated impact of supplementation of vitamin D during resistance training in 24 overweight and obese individuals. Intervention group who received vitamin D at the rate of 4000 IU per day against placebo, reported elevated vitamin D status was associated with reduced waist-to-hip ratio.…”
Section: Intervention Studiesmentioning
confidence: 98%
“…Intervention group who received vitamin D at the rate of 4000 IU per day against placebo, reported elevated vitamin D status was associated with reduced waist-to-hip ratio. The study revealed higher efficiency of vitamin D in lowering complications of obesity as compared to physical exercise [49]. Significant reduction in serum vitamin D concentration and secondary hyperparathyroidism was observed in severely obese patients following jejunal bypass surgery [50].…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Although supplemental vitamin D increases serum 25(OH)D, results regarding the influence of supplementation on muscle strength and physical performance are inconsistent [24][25][26][27][28][29][30]. In a previous investigation, supplemental vitamin D (4000 IU/d of cholecalciferol) enhanced strength recovery following (Post to 24-h) an exercise protocol that induced immediate and persistent deficits in muscle strength [31].…”
Section: Introductionmentioning
confidence: 95%